L’humanitaire islamique et les ONG musulmanes en France : quels registres de mobilisation ? - Lucas Faure (L’Année du Maghreb)
The present article will focus on Islamic humanitarian organisations, from their roots in the United Kingdom to their settlement in France, without neglecting the role of public authorities. Though this is often treated as a homogeneous field, the present article claims that French Islamic humanitarian organisations use different registers to mobilize and raise awareness for their causes in the context of Muslims’ minority status in France. Two ideal-type categories help to classify these mobilisations depending on whether they use a register of “assertion” or “contestation”. At first sight, the promotion of a “civil Islam” purged of its communitarian aspect, coupled with a mitigation of the religious dimension of the association, seems to offer more guarantees to be legitimized by and to establish partnerships with state authorities. Conversely, vehement speeches, and the promotion of a religious and intra-communitarian aid, would contribute to marginalizing Muslim NGOs. However, this study based on ethnography and participant observation in France (2017-2020), supplemented by interviews and an online enquiry, brings to light the ambivalent attitude of French authorities towards Muslim NGOs. By contrast with the republican rhetoric that stigmatizes faith-based differences, the French State entrusts Muslim associations with caring for Muslim beneficiaries. The injunctions imposed by the French State are thus twofold. Muslim NGOs are encouraged to minimize their confessional affiliation, but they are also incorporated within the State’s policy of intervention with sections of French society where Muslims are in a majority because of these NGO’s supposed “cultural proximity” and the sharing of a common Islamic identity.